A review of the Canthyporus exilis group, with the description of two new species (Coleoptera: Dytiscidae) - Bilton, David T. (Zootaxa, 2015)
Canthyporus namaqualacrimus sp. nov. and Canthyporus pallidus sp. nov. are described from the Namaqualand region of South Africa, both members of the exilis group. A revised key to species of the group is provided, together with details of the external and spermathecal tract morphology of the female of Canthyporus aenigmaticus Biström & Nilsson, 2006, a species previously known only from the male holotype. The opportunity is also taken to present new ecological and distributional data on members of the exilis group, most of which are primarily associated with springs and seepage habitats.